Novel lineages of Southern Ocean deep-sea foraminifera revealed by environmental DNA sequencing - Pawlowski, Jan
Diversity of deep-sea foraminifera is commonly studied based on analysis of agglutinated and calcareous tests preserved in the dried sediment samples. Soft-walled and agglutinated monothalamous (single-chambered) foraminifera are usually ignored because they are poorly preserved and difficult to identify. Moreover, the assemblage examined is usually limited to sediment size fraction larger than 63 or 125 mu m. To overcome these problems, we analysed the foraminiferal assemblage based on ribosomal DNA sequences amplified specifically from total DNA extracted from unsieved and fine fraction (<32 mu m of sediment samples from three sites in Southern Ocean. We obtained 392 sequences, representing 123 phylotypes of foraminifera. Over 90% of phylotypes (112) could not be assigned to any previously sequenced species or genera. Among these new phylotypes, 20 belong to the clade of multi-chambered calcareous Rotaliida and agglutinated Textulariida, while 94 branch among the radiation of monothalamous species. Many new phylotypes clustered together with other environmental foraminiferal sequences and sequences of unknown origin. Eight new lineages of environmental foraminiferal sequences (ENFOR 1-8) were distinguished. The morphology of species included in these novel lineages is unknown, but we can speculate that they are tiny, amoeboid protists present in the deep-sea sediments. Their diversity may be as high as that of better known large-sized foraminifera. Documenting this hidden component of deep-sea foraminiferal assemblages is a major challenge for the future. (C) 2011 Elsevier Ltd. All rights reserved.